Differences in the Alcohol Preference Assessment of Shy and Bold Zebrafish - Bellot, Marina Sanson; Guermandi, Isabela Inforzato; Camargo-dos-Santos, Bruno; Giaquinto, Percília Cardoso (Frontiers in Behavioral Neuroscience, 2022)
Individuals differ in their preference for alcohol and propensity to develop alcoholism, where the behavioral profile, such as the bold-shy axis, plays an important role for such a difference. However, literature is limited and conflicting on the causes and consequences of this relationship. Translational studies using animal models, such as zebrafish, can help identify behavioral traits that predispose individuals to drink alcohol compulsively. Here, the preference for alcohol was investigated in two distinct traits in zebrafish: shy and bold. For this purpose, fish were separated into shy and bold traits and then a conditioned place preference paradigm was used, a strategy that allows the rewarding effects from alcohol to be assessed by the ability to enhance the animal’s preference for an environment that initially was not preferred. It was found that bold zebrafish actively searched for the environment that was paired to alcohol after one acute exposure, whereas, shy fish changed their place preference even without alcohol administration, showing that the conditioned place preference protocol, given the short amount time to assess place preference, is not ample enough for shy fish to choose. Our results show that behavioral profiles must be considered in further studies since differences between shy and bold individuals on preference behavior can strongly interfere in the assessment of drug preference, mainly when using the conditioned place preference paradigm.